ADVANCED MATHEMATICS FORM 5 – DIFFERENTIATION

Share this post on:


DERIVATIVES

Slope of a curve

A curve has different slopes at each point. Let A, B, and C be different points of  a curve f (x)

edu.uptymez.com

Where ðx is the small increase in x

            ðy is the small increase in y

The slope of chord AC =edu.uptymez.com                    

If C moves right up to A the chord AC becomes the tangent to the curve at A and the slope at A is the limiting value of   edu.uptymez.com

edu.uptymez.com                                                               

Therefore

      edu.uptymez.com = edu.uptymez.com

edu.uptymez.com

The gradient at A is

edu.uptymez.com=edu.uptymez.com

edu.uptymez.com
or

edu.uptymez.com

This is known as differentiating by first principle

From the first principle

i)                   f(x)= x

edu.uptymez.com

edu.uptymez.com

edu.uptymez.com

edu.uptymez.com

ii)                f(x)= x2

edu.uptymez.com

edu.uptymez.com

edu.uptymez.com

edu.uptymez.com

iii)           f(x) =x3

edu.uptymez.com

edu.uptymez.com

edu.uptymez.com

edu.uptymez.com

edu.uptymez.com

iv)    f(x)= xn

edu.uptymez.com

edu.uptymez.com

edu.uptymez.com

By binomial series

edu.uptymez.com

edu.uptymez.com

edu.uptymez.com

edu.uptymez.com

edu.uptymez.com

In general

If edu.uptymez.com

 edu.uptymez.com

Example

Differentiate the following with respect to x

i)y = x2+3x

Solution

y =x2+3x
edu.uptymez.com

ii)    2x4+5
edu.uptymez.com

edu.uptymez.com
iii)edu.uptymez.com
   

edu.uptymez.com=edu.uptymez.com

edu.uptymez.com

Differentiation of products functions [ product rule]

Let y =uv

Where u and v are functions of x

If x   →   x+ðx

u     →    u +ðu

v     →   v+ðv

y     →    ðy +y

y= uv ……i)

Therefore

y+ðy = [ u+ðu][v+ðv]

y+ðy = uv +uðv+vðu +ðuðv….ii

Subtract (i) from (ii)

δy  =uðv +vðu +ðuðv

Therefore

edu.uptymez.com

  edu.uptymez.com

Therefore
edu.uptymez.com

Therefore
If y= uv

edu.uptymez.com    It is the product rule

Examples

Differentiate the following with respect to x

i)    y = [ x2+3x] [4x+3]

ii)    y = [ edu.uptymez.com +2] [x2+2]

Solution

Y = [x2+3x] [4x+3]

Let u = x2+3x

edu.uptymez.com = 2x+3

V = 4x+3

edu.uptymez.com

Therefore
edu.uptymez.com

=4x2+12x+8x2+12x+6x+9

=12x2+30x+9
edu.uptymez.com

ii)Let u =  edu.uptymez.com+2     edu.uptymez.com  →edu.uptymez.com

v = x2+2   edu.uptymez.com   edu.uptymez.com =2x

Therefore

edu.uptymez.com

edu.uptymez.com

edu.uptymez.com

Share this post on: